Fostering Climate Action and Resilience: Engaging the Local Community in a Living Lab - Kralj, Erik; Meulenberg, Cecil; Kumer, Peter (Komuniciranje okoljske krize, 2025)
This chapter examines the role of climate change communication within the framework of the Coastal City Living Lab, focusing on the Slovenian coastal town of Piran as a pilot area under the Horizon 2020 SCORE project. The study emphasizes the significance of community engagement and participatory governance in enhancing climate resilience in coastal urban areas vulnerable to sea-level rise, storm surges, and heatwaves. Through the Living Lab methodology, local stakeholders co-create adaptive solutions while communication strategies bridge scientific knowledge with public understanding. Key activities include knowledge transfer, capacity building, and consensus-building efforts designed to address climate risks specific to Piran. This chapter highlights the importance of communication in fostering stakeholder collaboration and sustaining climate resilience initiatives beyond project lifecycles, underscoring the critical need for locally grounded, inclusive adaptation measures in the face of escalating climate challenges.